"Amerikas schönste Geliebte" Prostitution und Frauenhandel in Havanna (1850-1925) - Hepke, Sabrina (Historamericana, 2022)
This volume describes the historical development of prostitution in Havana in connection with the social, political and economic developments between 1850 and 1925. Sabrina Hepke uses the debates among doctors, lawyers, social reformers and politicians to show the causes and dangers of prostitution in Havana.